Biomedical engineer density per hospital bed: A medical device quality indicator for Mexican Healthcare System - Luis G. Ayala; Nadezhda Aguilar Blas; Norma Patricia Navor Galeana (PLoS ONE, 2026)
Background The measurement of health indicators that enable the estimation of a system’s capacity to provide adequate patient care constitutes a highly relevant factor in the evaluation of healthcare systems. Traditionally, these indicators include variables such as physician density, nursing staff, and other human resources; however, a critical component that often receives less attention is the capacity of healthcare institutions to sustain high-quality infrastructure and medical technology, which are essential to ensuring the continuity, safety, and efficiency of healthcare services. In this context, an important complementary metric would be the density of biomedical engineers within hospital settings, as these professionals are required to design, evaluate, regulate, acquire, maintain, and manage medical technologies and healthcare infrastructure. Current WHO metrics measure biomedical engineer density per 10,000 inhabitants, not reflecting their direct relationship with medical devices and hospital infrastructure. Objective To develop a novel biomedical engineer density indicator per hospital beds ( ρBEhb ) that relates workforce capacity to medical devices rather than general population, and to evaluate its applicability within the Mexican healthcare system. Methods The ρBEhb calculates the ratio between biomedical engineers providing professional services (internal or mixed staff) and available hospital beds for a given year. The methodological framework follows PAHO/WHO ‘Health Indicators’ guidelines. Data from the Mexican healthcare system (2017–2022) were analyzed alongside international benchmarks. Results The Mexican healthcare system showed generally positive ρBEhb trends from 2017 to 2022, with a −0.53% decrease (2017−2018) and a notable 14.41% increase (2020−2021) coinciding with the SARS-CoV-2 pandemic. While Mexico's absolute number of biomedical engineers is comparable to the USA, ρBEhb analysis reveals a dual structural deficit — insufficient hospital beds and inadequate biomedical engineering workforce — when adjusted for population size and international standards. Conclusions The ρBEhb indicator exposes Mexico's dual deficit in hospital beds and biomedical engineers relative to population needs. This metric provides a more relevant measure for assessing medical device management capacity and healthcare quality than traditional population-based indicators.